BEGONIA CLADOTRICHA (BEGONIACEAE): A NEW SPECIES FROM LAOS - HUGHES, M. (Edinburgh Journal of Botany, 2007)
A new species of Begonia (Begoniaceae) is described from Khammouan Province in Laos. The new species, Begonia cladotricha M.Hughes, belongs in Begonia sect. Diploclinium, and is unusual amongst Asian Begonia in having basally branched hairs on all vegetative parts of the plant.
Keywords: Begonia; Laos; new species; trichome